Identification of a potent neurotrophic substance for ciliary ganglionic neurons in fetal calf serum as insulin-like growth factor II - Motoike, Toshiyuki; Unsicker, Klaus (Journal of neuroscience research, 1999)
When fetal calf serum (FCS) alone is used as a trophic support for cultured chicken parasympathetic ciliary ganglionic (cCG) neurons, it does not show any survival-promoting effects on these neurons. When FCS is applied to heparin-affinity chromatography, however, potent survival-promoting activity is obtained in the fraction eluted with 0.5 M NaCl. Using cCG neurons as a bioassay system, this neurotrophic activity was purified by a combination of heparin-affinity chromatography, gel filtration chromatography, and Sep-Pak C18 cartridge. The 40-50-kDa fractions from the gel filtration column with strong survival-promoting activity were shown to contain insulin-like growth factor II (IGF-II) by immunoblot analysis. By acidification, the survival-promoting activity and IGF-II were translocated together from the 40-50-kDa to the 7-10-kDa fractions, and the survival-promoting activity in the 7-10-kDa fractions was blocked by an anti-IGF-II neutralizing monoclonal antibody. These results indicate that the neurotrophic substance in 0.5 M NaCl-eluate from heparin-affinity chromatography is IGF-II and that mechanisms may exist in vivo for the activation of latent IGF-II, whose biological effects may be blocked by its specific binding proteins. J. Neurosci. Res. 56:386-396, 1999. © 1999 Wiley-Liss, Inc.
Gesehen am 24.11.2016